Small Business Marketing Strategy : Increasing Product Competitiveness based Wisdom Local through Digital Marketing (MSMEs in Sungai Penuh City ) - Melifia Liantifa; Anggia Ayu Lestari (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Sungai Banyak City, Jambi Province, play a crucial role in the local economy, particularly in the development of products based on local wisdom. These products, which include handicrafts, traditional foods, and traditional clothing, have significant potential but often struggle with marketing and competitiveness. In today's digital era, implementing digital marketing is an effective solution for increasing the competitiveness of MSME products, introducing them to a wider market, and strengthening local cultural identity. This study aims to analyze digital marketing strategies that MSMEs in Sungai Banyak City can implement to enhance the competitiveness of products based on local wisdom. The approach used is descriptive qualitative research, with data collection methods through in-depth interviews, field observations, and documentation studies. The results indicate that MSMEs in Sungai Banyak City have significant potential for developing products based on local wisdom, but are constrained by limited digital knowledge, technological infrastructure, and human resource skills in online marketing. Digital marketing training, the use of social media, and e-commerce optimization are some of the recommended strategies that can strengthen product competitiveness. This research also suggests the importance of collaboration with influencers and local communities, as well as government support, to overcome challenges and capitalize on opportunities in digitally marketing MSME products. It is hoped that this digital marketing strategy will increase the visibility, marketability, and competitiveness of MSME products based on local wisdom in Sungai Banyak City.